The Influence of Entrepreneurship Learning and the Social Environment on Students' Interest in Entrepreneurship (Case Study of Students at Medan State Polytechnic and Seberang Perai Polytechnic, Malaysia) - Nasution, Harris Pinagaran; Safaruddin; Fitri, Nursiah; Purnami, Suri; Yusoff, Rohani Binti M.M; Omar, Nurul Ihsaniah Binti; Ahmad, Azura Binti (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Entrepreneurship learning is a technique prepared through teachers for students on a way to advantage and procedure understanding, capabilities and attitudes. The social surroundings is one of the elements which could influence someone or organization to do so and trade the behavior of every person. This study seeks to gather real-world proof of how much students' interest in entrepreneurship at Medan State Polytechnic and Seberang Perai Polytechnic in Malaysia is affected by the entrepreneurship learning program and the social environment. The descriptive quantitative method was employed for this research, involving a sample of 75 Polmed students and 76 PSP students from Malaysia, making a total of 151 participants. The analysis method utilized multiple linear regressions with SPSS version 25 to process the data statistically. The findings indicate that both entrepreneurial learning and the social environment significantly impact students' interest in entrepreneurship among Polmed and PSP students in Malaysia. The adjusted R Square test revealed a coefficient of determination of 0.776, suggesting that 77.6% of the entrepreneurial interest at Medan State Polytechnic and Malaysian State Polytechnic could be attributed to entrepreneurial learning and the social environment, while 22.4% might be influenced by unexamined variables in this research.